Tumor irradiation induced immunogenic response: the impact of DNA damage induction and misrepair - Qi Liu; Xiaoran Shi; Nilupaier Tayier; Lin Ma (Radiation Oncology)
Abstract Focal tumor irradiation, a cornerstone of cancer therapy, has been increasingly recognized for its capacity to provoke systemic immunogenic responses that extend beyond localized tumor control. Recent advances highlight DNA damage, especially DNA double-strand breaks (DSBs), as a central mediator linking radiotherapy to anti-tumor immune activation. Importantly, DNA misrepair, prevalent in cancer cells with deficient or dysregulated repair machinery, serves as a double-edged sword: while fostering tumor adaptation and genomic instability, it also fuels immune recognition through the accumulation of neoantigens, extracellular DNA release, immunogenic cell death, and the modulation of immune-related cytokines and chemokines. This review critically synthesizes the latest clinical and preclinical insights into the dynamic interplay between DNA damage, repair fidelity, and the immunogenic consequences of tumor irradiation. By focusing on the impact of DSB induction and misrepair processes, we underscore the emerging therapeutic opportunities of modulating DNA repair pathways during radiotherapy to potentiate anti-tumor immunity, particularly in synergy with immune checkpoint blockade. This article provides a comprehensive perspective on the molecular underpinnings and translational potential of harnessing irradiation-induced immunogenicity, offering a roadmap for future therapeutic strategies in radiation oncology and cancer immunotherapy. Clinical trial number Not applicable